HISTORICAL CONDITIONS, CURRENT ACHIEVEMENTS, AND FUTURE PROSPECTS OF SPORTS INFRASTRUCTURE IN UZBEKISTAN - Atashov Marat Tenelbayevich (Bright Mind Publishing, 2025)
The development of sports infrastructure in Uzbekistan has become a focal point for promoting physical education and enhancing the overall health and wellbeing of its citizens. This article examines the historical context, current advancements and future prospects of sports infrastructure in Uzbekistan. By analyzing government initiatives, international collaboration and investments in facilities and programs, we aim to provide a comprehensive overview of how these efforts contribute to the nation’s physical education landscape and the broader goals of social cohesion and national pride.
Keywords: Sports infrastructure, physical education, development, health, government initiatives, international collaboration.